A Method to Access Symmetrical Tetrasubstituted Pyridines via Iodine and Ammonium Persulfate Mediated [2+2+1+1]‐Cycloaddition Reaction. Issue 9 (22nd February 2017) - Liu, Weibing; Tan, Hua; Chen, Cui; Pan, Yupeng
Abstract: A novel metal‐free [2+2+1+1]‐cycloaddition method for rapid and productive preparation of symmetrical 2, 3, 5, 6‐tetrasubstituted pyridines has been developed from α‐substituted arones and N, N‐dimethyl formamide (DMF) using iodine (I2 ) and ammonium persulfate ((NH4 )2 S2 O8 ) as mediators. In this process, both DMF and (NH4 )2 S2 O8 play a dual role for the formation of pyridines. DMF acts as the reaction medium and the C4 source (the methyl group of DMF), while (NH4 )2 S2 O8 serves as the oxidant and nitrogen resource. Notably, this transformation exhibited a broad substrate scope towards a wide variety of different arones to give the corresponding tetrasubstituted pyridines in moderate to excellent yields. Abstract :